Circulating cell-free DNA as a potential marker in smoke inhalation injury. Issue 12 (March 2019) - Hayun, Yehiel; Shoham, Yaron; Krieger, Yuval; Silberstein, Eldad; Douvdevani, Amos; Ad-El, Dean
Abstract : Abstract: Failure in evaluation of smoke inhalation injury (SII) is related to increased morbidity and mortality. Prognostic biomarkers that reflect the injury are undoubtedly needed. Cell-free DNA (CFD) concentrations are associated to the extent of tissue damage and inflammation in various pathologies. We have developed a simple assay for CFD quantification and previously found it prognostic in various pathologies including burns, lung disease, and sepsis. The aim of this study was to evaluate admission CFD as an injury severity marker in patients with SII. In a prospective study, we measured admission CFD levels in 18 SII patients and matched control subjects. Daily CFD levels were also performed in 4 hospitalized patients. Serum CFD levels were measured by our direct rapid fluorometric assay. Admission CFD levels of SII patients were significantly higher than those of healthy controls, 879 (236–3220) ng/mL vs. 339 (150–570) ng/mL, [median (range)], P  < .0001. Admission CFD levels of hospitalized patients were significantly higher than those of nonhospitalized patients, 1517 (655–3220) ng/mL vs. 675 (236–1581) ng/mL, P  < .05. Admission CFD positively correlated with hospitalization time (Rho = 0.578, P  < .05) and was in linear correlation with CO poisoning (carboxyhemoglobin (COHb) levels, R 2  = 0.621, P  < .0001). Additionally, along with the recovery of hospitalized patients, we observed a matched reduction of CFD levels. CFD appears to be a potentially valuable marker for severity and follow-up of SII. We believe this rapid assay can help introduce the routine use of CFD measurement into daily practice.